Phosphorylase: control and activity. - Jenkins, J; Johnson, L; Stuart, D; Stura, E; Wilson, K; Zanotti, G (1981)
Recent results from the crystallographic studies on glycogen phosphorylase b at 2 A resolution are reviewed with special reference to other themes of the meeting. The structural similarity of the fold of 150 residues in phosphorylase to the observed in lactate dehydrogenase is discussed and the binding sites for NADH in phosphorylase are described. The binding of the potent inhibitor glucose-1,2-cyclic phosphate to phosphorylase b in the crystal has been studied at 3 A resolution. The results are compared with those previously obtained for glucose-1-phosphate and discussed with reference to proposals for a mechanism of catalysis that involves the essential cofactor pyridoxal phosphate.